2022
DOI: 10.3390/ijerph20010793
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nutrition and Forest-Bathing in the Physical Rehabilitation of Physically Inactive Patients: From the Molecular Aspects to New Nature-Inspired Techniques

Abstract: Physical rehabilitation plays a fundamental role in the management of individuals with disabilities associated with age-related muscle loss or affected by catastrophic conditions such as trauma, surgery, cancer or other severe pathologies. These events have in common an extended period of physical inactivity. Patients who undergo prolonged bed rest often present with a number of complications; for example, muscle loss that can exacerbate existing conditions determined by sarcopenia, which in turn greatly limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…In addition, Ochiai et al [104] measured the psychophysiological effects of nature therapy (stimulation with bonsai trees) on adult male patients with spinal cord injuries and found that forest bathing can lead to a state of physiological and psychological relaxation in patients with spinal cord injuries. The above studies suggest the possibility of forest bathing being applied as a rehabilitative medicine, as suggested by another study [105]. However, further studies in this area are needed.…”
Section: Forest Bathing May Apply To Rehabilitation Medicinementioning
confidence: 58%
“…In addition, Ochiai et al [104] measured the psychophysiological effects of nature therapy (stimulation with bonsai trees) on adult male patients with spinal cord injuries and found that forest bathing can lead to a state of physiological and psychological relaxation in patients with spinal cord injuries. The above studies suggest the possibility of forest bathing being applied as a rehabilitative medicine, as suggested by another study [105]. However, further studies in this area are needed.…”
Section: Forest Bathing May Apply To Rehabilitation Medicinementioning
confidence: 58%
“…In both cases, the effect of physical activity on the athlete's movement asymmetries will depend on genetic factors such as sensitivity to pain, predisposition to injury, injury recovery rate as well as muscle strength and elasticity. Other important factors include nutrition [75,76], and previous injuries. Health/fitness professionals are likely to face future challenges in how to optimise exercise training for individuals with desirable genes, as well as for motivating individuals without them to begin and/or continue exercising [77].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there is a growing demand to create novel antimicrobial drugs that can combat the emergence of resistance and reduce the need for antibiotics [ 1 ]. Various bioactive chemicals can be obtained from medicinal plants [ 6 , 7 , 8 , 9 , 10 ], and numerous techniques have been employed to investigate their potential as antimicrobial agents [ 11 ]. These bioactive compounds are secondary plant metabolites, representing one of the unexplored sources of antimicrobial agents in nature [ 12 ].…”
Section: Introductionmentioning
confidence: 99%